{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

527solns9

# 527solns9 - 642:527 SOLUTIONS ASSIGNMENT 9 FALL 2007...

This preview shows pages 1–2. Sign up to view the full content.

642:527 SOLUTIONS: ASSIGNMENT 9 FALL 2007 Section 9.9: 2 (a) See text solution. (d) The formula is (23) of the text. We have ( e 1 , e 1 ) (= e 1 · e 1 ) = 14, ( e 2 , e 2 ) = 5, ( e 3 , e 3 ) = 70, ( e 1 , u ) = 8, ( e 2 , u ) = 5, and ( e 3 , u ) = 10, so u = (4 / 7) e 1 + e 2 + (1 / 7) e 3 . 12 (d) See text solution. (f) Summary of the Gram-Schmidt process: Given v 1 , . . ., v n we define ˆ e 1 = v 1 / bardbl v 1 bardbl . Now, once we have defined ˆ e 1 , . . . ˆ e k we define ˆ e k +1 by a two-step process: e k +1 = v k +1 k summationdisplay i =1 ( ˆ e i , v k +1 ) ˆ e i , ˆ e k +1 = e k +1 bardbl e k +1 bardbl . So for the given vectors v 1 = (1 , 1 , 1), v 2 = (1 , 0 , 1), v 3 = (1 , 1 , 0) we have ˆ e 1 = v 1 bardbl v 1 bardbl = 1 radicalbig ( v 1 , v 1 ) v 1 = 1 3 (1 , 1 , 1); e 2 = v 2 − ( ˆ e 1 , v 2 ) ˆ e 1 = (1 , 0 , 1) 2 3 (1 , 1 , 1) = 1 3 (1 , 2 , 1) , ˆ e 2 = e 2 bardbl e 2 bardbl = 1 6 (1 , 2 , 1); e 3 = v 3 − ( ˆ e 1 , v 3 ) ˆ e 1 − ( ˆ e 2 , v 3 ) ˆ e 2 = (1 , 1 , 0) 2 3 (1 , 1 , 1) + 1 6 (1 , 2 , 1) = 1 2 (1 , 0 , 1) , ˆ e 3 = e 3 bardbl e 3 bardbl = 1 2 (1 , 0 , 1); Section 9.10: 2 (a) See text solution. (c) With u = (3 , 0 , 1 , 4 , 1) we have ( ˆ e 1 , u ) = 5 / 5, ( ˆ e 2 , u ) = 6 / 6, ( ˆ e 3 , u ) = 4, so the best approximation is 3 summationdisplay i =1 ( ˆ e i , u ) ˆ e i = (1 , 0 , 2 , 0 , 0) + (2 , 0 , 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}